2008
DOI: 10.1523/jneurosci.3213-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Causes Maturation-Dependent Cell Death in the Developing White Matter

Abstract: Periventricular leukomalacia is the predominant injury in the preterm infant leading to cerebral palsy. Oxygen exposure may be an additional cause of brain injury in these infants. In this study, we investigated pathways of maturation-dependent oligodendrocyte (OL) death induced by hyperoxia in vitro and in vivo. Developing and mature OLs were subjected to 80% oxygen (0 -24 h). Lactate dehydrogenase (LDH) assay was used to assess cell viability. Furthermore, 3-, 6-, and 10-d-old rat pups were subjected to 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 56 publications
13
145
0
4
Order By: Relevance
“…In contrast, this normalization was not seen among HI+hyperoxia, possibly indicating an irreversible effect of hyperoxia on immature white matter. This is in agreement with emerging evidence of selective vulnerability of white matter to prolonged hyperoxia exposure during the first postnatal week in rats (29), leading to long-term reduction in FA of corpus callosum (32). The observation of activated microglia in white matter supports the hypothesis that these cells, abundant in developing white matter, are key effectors in the pathogenesis of injury to perinatal white matter (4).…”
Section: Dtisupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, this normalization was not seen among HI+hyperoxia, possibly indicating an irreversible effect of hyperoxia on immature white matter. This is in agreement with emerging evidence of selective vulnerability of white matter to prolonged hyperoxia exposure during the first postnatal week in rats (29), leading to long-term reduction in FA of corpus callosum (32). The observation of activated microglia in white matter supports the hypothesis that these cells, abundant in developing white matter, are key effectors in the pathogenesis of injury to perinatal white matter (4).…”
Section: Dtisupporting
confidence: 87%
“…White matter deviations are often seen in preterm infants (28), and both hypoxia and ischemia, as well as hyperoxia, are thought to play an important role in the pathogenesis (4,29). During normal maturational development of white matter in rats, increasing FA and decreasing radial diffusivity observed during the first postnatal weeks are thought to be related to increasing oligodendrocyte coverage and myelination of white matter tracts (30,31).…”
Section: Dtimentioning
confidence: 99%
“…Carboxy-DCFDA is a cellpermeable nonfluorescent dye that is oxidized into highly green fluorescent DCF in the presence of oxidants, including ROS. The intensity of fluorescence of DCF generated from carboxy-DCFDA is proportional to the amount of ROS in cells (Pérez-Severiano et al, 2004;Kirkland et al, 2007;Gerstner et al, 2008;Vaughn and Deshmukh, 2008). We found that both WT and HD 140Q/140Q neurons exhibited DCF signal in the somata and neurites.…”
Section: Hd Neurons Have Elevated Levels Of Reactive Oxygen Speciesmentioning
confidence: 71%
“…It has been observed in experimental animals that hyperoxemia increases apoptotic cell death and white matter damage (14,15). The vulnerability to oxygen-induced cell death is age dependent and the maximal incidence is observed during the first week of life (16).…”
Section: Discussionmentioning
confidence: 99%